Adaptive Principal Leadership in Building Competitive Schools in the VUCA Era in SMP Negeri 4 Jombang - Kustomo Kustomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era requires schools to respond effectively to rapid and dynamic changes. In this context, adaptive principal leadership plays a crucial role in managing change, fostering innovation, and strengthening school competitiveness. This study aims to examine how adaptive principal leadership contributes to building a competitive school through a case study at SMP Negeri 4 Jombang, Indonesia. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and document analysis involving the principal, vice principals, teachers, administrative staff, and the school committee, selected using purposive sampling. Data credibility was ensured through source and technique triangulation, while analysis followed the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the principal demonstrated adaptive leadership by making responsive decisions, empowering human resources, fostering a collaborative school culture, and promoting continuous innovation. School transformation was supported by the integration of digital technologies into learning and school services, including Smart TVs in classrooms, Chromebooks, QR code-based e-books, QRIS digital payment systems, and coding and artificial intelligence education. Furthermore, an adaptive and collaborative school culture enhanced teacher competence, improved educational service quality, strengthened school governance, and increased public trust. The study concludes that adaptive principal leadership is a key driver in developing innovative, resilient, and competitive schools in the VUCA era through digital transformation, organizational culture development, and collaborative engagement among all school stakeholders.